2024
DOI: 10.24084/repqj13.455
|View full text |Cite
|
Sign up to set email alerts
|

A fault detection method for pitch actuators faults in wind turbines

Abstract: Abstract.The paper presents a model-based fault detection method for pitch actuators faults using the normalized gradient method to estimate the parameters of the pitch actuator. One major difficulty is that the input signal to the parametric estimation method must be a persistent excitation. To circumvent this, a chattering term is added to the pitch control law and the usual low-pass filters are not used for the parametrization in the normalized gradient method (thus acceleration information is used). In ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Regarding fault detection and diagnosis for wind turbines, there are different models and methods developed which can be generally categorized as model-based [3][4][5][6] and databased [6][7][8][9][10][11][12][13] approaches. The model-based approach is mainly used for fault mechanism analysis, and the data-based approach is for condition assessment and prediction.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding fault detection and diagnosis for wind turbines, there are different models and methods developed which can be generally categorized as model-based [3][4][5][6] and databased [6][7][8][9][10][11][12][13] approaches. The model-based approach is mainly used for fault mechanism analysis, and the data-based approach is for condition assessment and prediction.…”
Section: Introductionmentioning
confidence: 99%
“…The damage to the pitch system not only increases the operation and maintenance cost, but also reduces the production efficiency of the wind turbine [7]. In recent years, there are a number of studies reported on fault diagnosis and prediction for wind turbine pitch system, e.g., References [7][8][9][10][11][12][13][14]. Based on literature survey, it is found that the published studies can be generally classified into two categories: One is physical model-based approach, e.g., References [12][13][14][15] and the other is based on measurement data, e.g., References [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…A set of possible faults affecting system dynamics is described. In Reference [13], a model-based variable pitch actuator fault detection method is proposed. When the pitch actuator is dynamically changed, the normalized gradient method is used to estimate the parameters of the pitch actuator and obtain the residual signal.…”
Section: Introductionmentioning
confidence: 99%